(untitled) (Texas Journal of Medical Science, 2023)
The study included 103 patients hospitalized for SARS-CoV-2 pneumonia at the Bukhara Regional Infectious Diseases Hospital, which was reorganized into the Covid Center. Immunological studies of the blood of sick children were carried out in the laboratory of immunomorphology of the Institute of Human Immunology and Genomics of the Academy of Sciences of the Republic of Uzbekistan. The indicators of interferon (INF-a, IFN-γ), cytokines (IL4, IL18) and biochemical tests in the blood were studied. In patients with SARS-CoV-2 pneumonia and type 2 diabetes, total bilirubin has a high relationship with the diabetogenic cytokine IL-18 - r = 0.42, against the background of a noticeable negative relationship with IL-4 (r = -0.30) and INF γ -r=-0.34. At the same time, the free fraction of bilirubin, like total bilirubin, has noticeable negative connections with IL-4 (r = -0.22) and IFN-γ r = -0.34, and has a significant positive connection with IL-18 - r = 0.34